The EFL Students’ Critical Reading Skills Across Cognitive Styles - Leonardus Par (JEELS (Journal of English Education and Linguistics Studies), 2018)
This study aims to explore the difference between the field independent (FI) and field dependent (FD) learners in the area of EFL critical reading skills. To this end, 60 undergraduate EFL students who had taken and passed the Critical Reading course involved as the subjects. The Group Embedded Figure Test (GEFT) was administered to classify the students’ cognitive styles into FI and FD groups. Furthermore, to measure the students’ critical reading skills, the critical reading comprehension test (CRCT) in the form of multiple choice questions was developed and administered. The test items were focused on assessing students’ analytical and inferential skills of reading texts, specifically on determining the main idea, the purpose, the tone, making an inference and taking conclusion. The findings indicate that there is a statistically significant difference in the critical reading skills between FI and FD students. More specifically, the differences are in determining the main idea, determining the purpose, making an inference, and taking the conclusion of the texts in the CRCT. Pedagogically, selecting appropriate reading texts to be used in Critical Reading course practice for developing the students’ critical reading skills will be beneficial for both of FI and FD students.